Analisis Perubahan Garis Pantai Menggunakan Citra Multitemporal Google Earth Pro Di Desa Kuta, Kecamatan Kuta, Kabupaten Badung Tahun 2014-2023 - pratiwi, ni luh adhelia fajar; Atmaja, Dewa Made; Putra, I Wayan Eka Krisna (Jurnal Ilmiah Wahana Pendidikan, 2025)
Shoreline changes are a significant phenomenon in the coastal area of ​​Kuta Village, Kuta District, Badung Regency, which is a strategic area for tourism and economy. Therefore, an analysis of shoreline changes in Kuta Village is needed to determine how far the changes have occurred during the period 2014-2023. The purpose of this study was to analyze parameters and map shoreline changes in Kuta Village. The method used is On Screen Digitization with Digital Shoreline Analysis System (DSAS) calculations. The results of this study are as follows: 1) NSM shows total abrasion reaching -3482.84 meters, while accretion is only 11.82 meters, with a total change of -3471.02 meters. 2) EPR shows the rate of abrasion change of -390.11 m/year for accretion of 1.31 m/year, with a total of -388.8 m/year. 3) The results of the Net Shoreline Movement (NSM) value show that the coastline experienced abrasion of 8,678 ha from 2014-2023 and experienced accretion of 0.0313 ha from 2014-2023.